FACTORS OF FUNCTIONING AND DEFINING OF SCALE AND PERSPECTIVES OF DEVELOPMENT OF FINANCIAL SECTOR - Барановський , Олександр; Барановська , Вікторія (Socio-economic relations in the digital society, 2019)
Importance of the research of the determinants of the functioning and development of the financial sector, explicit quantity and quality assessment of its size and impact on the national economy conditions is substantiated. It is highlighted that the establishment and the development of the fi nancial sector are stipulated by the financial globalization and are made under the global integration and the increase of the capitalization of the financial institutes, change of their functions, enlarging of the spectrum and improvement of the quality of financial products proposed by them, increase in the competition within the industry, among industries and international competition. Factors of the functioning and ways of the defi ning of the scale and perspectives of the development of the financial sector of the national economy are specifi ed. Author’s view on the determinants of the functioning and the development of the financial sector of the national economy is presented. Ways of defi ning the impact of the size of the financial sector on the national economy conditions are analyzed. Factors of the signifi cant gap between the financial and the real sectors of the economy and the researchers' views on assessment of the development of the financial sector of the national economy as well as the author’s view on the factors of such development are stated. Problems of the development of the financial sector of the national economy are substantiated. Internal limitations of macroeconomic, institutional and structural character which slow stable development of the financial sector are defined.
Keywords: financial sector; factors of functioning of financial sector; scale and perspectives of development of financial sector; assessment of development of financial sector; real sector of national economy